Yukon First Nations Youth Mental Wellness: The Development of Culturally Appropriate Healing. - Carlick, Melissa (Author); Mills, Antonia (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2011)
The purpose of this thesis is to examine Indigenous versus Western philosophies that pertain to treatment of mental health and wellbeing for Indigenous youth in the Yukon. This thesis is framed by two questions about the experience of identity for Yukon First Nations Youth: (1) How are Yukon First Nations Youth able to develop and sustain their individual and collective identity by balancing the two worlds they live in? And (2) What is the Yukon First Nations perspective on spirituality, mental health and Youth suicide prevention? It is pertinent that a distinction be made between what has been implemented in health care and seen as the social norm in terms of the Western use of power versus emphasis on spiritual truth. The words Spirituality and Healing are synonymous to Indigenous philosophies of wellness. There is a need for culturally appropriate healing approaches in the Yukon. This thesis focuses on solutions for the First Nations youth in the Yukon, as described by two Elders, two service providers, a mom and a dad, and the two youth that I talked to, thus taking a unique and insightful approach. The questions they were asked have identified how these people view youth developing and sustaining their individual and collective identity by balancing the two worlds they live in. --P. v. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1737770